Introduction of “MAPS” wound healing index and its correlation with guided bone regeneration outcome - Amanda Rodriguez; Diego Velasquez; Leonardo Marquez; Jose Maria Ramos; Nataly Zambrana; Maria Masotti; Oliver Kripfgans; Hsun-Liang Chan (PLoS ONE, 2025)
This study aims to introduce a new index that could become a framework for future modification and improvement, and retrospectively test the predictability of this index collectively and individually for final bone changes by using existing research data pertinent to guided bone regeneration (GBR). Methods The MAPS score was introduced to evaluate the bioMechanical, Aesthetic/Anatomical, Pathophysiologic, and Subject-related parameters for the healing assessment of 20 patients who underwent GBR in the posterior mandible retrospectively. Intraoral photography was taken at 3-, 10-, 21 days, and 5 months, resulting in 80 follow-up visits. Two independent examiners evaluated the photos giving scores for each timepoint and tested against horizontal bone gain (CBCT) for predictability. Results Cohen’s Kappa values showed high intra- and inter-examiner agreement. Pearson’s correlation showed an inverse correlation between baseline bone width and bone changes at a 3 mm level (R2 = 0.23). The higher M, A, and P values at any time point were associated with higher bone gain. The 10-day MAPS score turns out the most predictive of bone gain (RMSE 1.32, R2 0.75). In addition, increasing the average P score by 1 point at 10 days is associated with an increase in bone gain of 1.23 (p=.057). Conclusion The MAPS score improves consistently over the 5-month healing period. However, no statistically significant difference is observed between the scores at 21 days and 5 months, reflecting the clinical healing pattern for GBR. The overall MAPS score correlated with bone changes after GBR procedures, indicating its potential for estimating hard tissue regenerative outcomes.